Effects of Nemacystus decipiens polysaccharide on mice with antibiotic associated diarrhea and colon inflammation. Issue 3 (23rd January 2023) - Pan, Haoyu; Chen, Xia; Wang, PeiPei; Peng, Junfeng; Li, Judong; Ding, Kan
Abstract : Antibiotic associated diarrhea (AAD) is a common side effect of antibiotic therapy in which gut microbiota plays an important role in the disease. Abstract : Antibiotic associated diarrhea (AAD) is a common side effect of antibiotic therapy in which gut microbiota plays an important role in the disease. However, the function of gut microbiota in this disease is still not entirely clear. Polysaccharides have shown strong activity in shaping gut microbiota. Whether the polysaccharide can intervene with the microbiota to improve ADD has not been determined. In this study, we extract crude polysaccharides from Nemacystus decipiens ( N. decipiens ), a traditional Chinese medicine (TCM), named NDH0. The crude polysaccharide NDH0 might significantly relieve the symptom of mice with AAD, including a reduction in body weight, shortening of cecum index and the infiltration of inflammatory cells into the colon. NDH0-treated mice exhibited more abundant gut microbial diversity; significantly increased the abundance of Muribaculum, Lactobacillus, and Bifidobacterium and decreased the abundance of Enterobacter and Clostridioides at genus level. NDH0 treatment down-regulated the level of pro-inflammatory cytokines, including IL-1β and IL-6 in colon tissue. NDH0 protected the integrity of colon tissues and partially inactivated the related inflammation pathway by maintaining occludin and SH2-containing Inositol 5′-Phosphatase (SHIP). NDH0 could alleviate symptoms of diarrhea by modulating gut microbiota composition, improving intestinal integrity and reducing inflammation. The underlying protective mechanism was to reduce the abundance of opportunistic pathogens and maintain SHIP protein expression. Collectively, our results demonstrated the role of NDH0 as a potential intestinal protective agent in gut dysbiosis.